Preparation, characterization and crystal structure of dinuclear zinc(II) carboxylate complex with 1-(pyridin-4-yl)ethanone and 4-methylbenzoate based ligands - Cimen, Efdal; Gumus, Ilkay; Celik, Omer; Keskin, Ebru; Arslan, Hakan (European Journal of Chemistry, 2016)
The centrosymmetric binuclear complex, [Zn2(C8H7O2)4(C7H7NO)2], has been synthesized and characterized by FT-IR and NMR methods. The obtained Zn(II) metal complex has been also characterized by a single crystal X-ray diffraction study. Crystal data for C46H42N2O10Zn2: Monoclinic, Space group P21/c (no. 14), a = 10.4827(3) Å, b = 8.6141(2) Å, c = 24.7582(6) Å, β = 101.066(1) °, V = 2194.07(10) Å3, Z = 4, Dcalc = 1.383 g/cm3, 22545 reflections measured (3.96° ≤ 2Θ ≤ 52.74°), 4465 unique (Rint = 0.0388, Rsigma = 0.0333) which were used in all calculations. The final R1 was 0.0489 (I ≥ 2s(I)) and wR2 was 0.1533 (all data). The four nearest oxygen atoms around each zinc ion form a distorted square-planar arrangement, and the distorted square-pyramidal coordination is completed by the nitrogen atom of the 1-(pyridin-4-yl)ethanone compound.